Barriers and enablers to skin-to-skin contact at birth in healthy neonates - a qualitative study - Amala James Alenchery; Joanne Thoppil; Carl Denis Britto; Jimena Villar de Onis; Lavina Fernandez; P. N. Suman Rao (BMC, 2018)
Abstract Background Skin to skin contact (SSC) at birth is the standard of care for newborns without risk factors. However, implementation of SSC at birth has been far from optimal. A qualitative study was undertaken to determine the barriers, enablers and potential solutions to implementation of SSC at birth in healthy newborn infants in a level III neonatal-care facility in Bangalore, India. Methods Consultants and residents/postgraduates (PG) from the departments of Obstetrics (n = 19) and Pediatrics (n = 14) and nurses (n = 8) in the labor room (LR) participated in the study. In depth interviews (IDI) and focus group discussions (FGD) were carried out with an interview guide and a moderators' guide containing inbuilt probes. Subjects of FGD were homogenous. All IDI and FGD were audio-taped, transcribed and analyzed using N VIVO version 9 (using free and tree nodes). Two authors separately coded the transcripts. Major and minor themes were identified. Rigor was ensured by triangulation and theoretical saturation. Informed consent and ethical approval was obtained. Results All subjects were aware of SSC at birth, some of its benefits and had practiced SSC. The major barriers identified were lack of personnel (nurses), time constraint, difficulty in deciding on eligibility for SSC, safety concerns, interference with clinical routines, and interdepartmental issues. Recall of an adverse event during SSC was also a major barrier. Furthermore, we found that most participants considered 1 h as impractical; and promoted 5-15 min SSC. Minor themes were gender bias of the newborn and cultural practices. The participants offered solutions such as assigning a helper exclusively for SSC, allowing a family member into the LR, continuing SSC after initial routines, antenatal counselling, constant reminders in the form of periodic sessions with audiovisual aids or posters in the obstetrics ward, training of new nurses and PG, and inclusion of SSC in medical and nursing curriculum. Conclusions The major barriers to SSC at birth are lack of personnel, time constraint and safety concerns. Training, designated health personnel for SSC and teamwork are the key interventions likely to improve SSC at birth.